Indoor Female Sex Workers’ Experiences of Counselling: A Hermeneutical Phenomenological Exploration - Velez, Camila; Audet, Cristelle (Canadian Journal of Counselling and Psychotherapy, 2019)
The counselling needs of sex workers remain largely invisible in the counselling literature despite sex workers identifying a range of mental health concerns, some of which are tied to the criminalization of sex work. This hermeneutic phenomenological study explored the counselling experiences of female indoor sex workers in Canada. The experiences of 6 participants are presented, based on descriptions obtained through semi-structured interviews. Results reveal 9 themes generated within 3 categories that were explored related to sex workers’ experiences of counselling: (a) initiating counselling, (b) the therapeutic relationship, and (c) disclosing sex work to the counsellor. Findings indicate that sex workers’ presenting concerns fall on a continuum regarding the relevancy to sex work. Beneficial and hindering aspects of the therapeutic relationship and disclosure of sex work are identified, emphasizing the importance of culturally-sensitive practice with sex workers. Implications for practice and future research are discussed.